The comparison of cellulase activities from bacteria and molds isolated from termites - Tresnawati Purwadaria; Pesta A Marbun; Arnold P Sinurat; Pius P Ketaren (Jurnal Ilmu Ternak dan Veteriner, 2003)
Screening for choosing the best bacterium and mold producing cellulase was carried out from eight xylanolytic bacteria and three cellulolytic molds isolated from termites. Each bacterium and mold was inoculated on the agar medium containing minerals and carboxymethylcellulose. The diameters of colony and clearing zones were measured after stained with Congo red. Four bacteria: Bacillus larvae XB 1-1, B. larvae XU 2-2, Bacillus PU 2-2, and B. pumilus PU 4-2 showing higher clearing zone ratio were further submerged cultured in PM medium containing 2% wheat pollard in the shaker incubator at room temperature, 150 rpm for 36 and 48 hours. The three molds: Aspergillus flavus S 13, MS 21, and Penicillium nalgiovense S 11 were also cultured in the same way as bacteria, but in Mandels medium containing 2% wheat pollard for three and five days incubation time. B. pumilus PU 4-2 and A. flavus S 13 produced the highest CMCase in each group respectively. All enzyme assays of A. flavus S 13 had higher activities than that of B. pumilus PU 4-2. The specific activity of CMCase, avicelase, FPase, and cellobiohidrolase were the highest on the enzyme of A. flavus S 13 produced from 3 days incubation time, while its β- glucosidase was the best for five days incubation. In term of activities, A. flavus S 13 had the highest ability to produce cellulase. The ability of B. pumilus PU 4-2 to produce cellulase and xylanase at the same time was an additional value.   Key words: Bacillus pumilus, Aspergillus flavus, cellulases